Klasifikasi, Fungsi, dan Relevansi Metode Pembelajaran PAI - Fikriyah, Shofiatul; Nafisa Ega Nuzula2 (PT. Banjarese Pacific Indonesia, 2024)
The educational curriculum continues to change and adapt as time goes by. Learning methods as an element in the curriculum also need to be developed so that they can always be relevant. Therefore, in this research the author wants to examine the classification, function and relevance of Pendidikan Agama Islam (PAI) learning methods. The results of this research state that the classification of learning methods is a grouping of methods used by teachers to interact with students so that the learning process can run effectively. Several other things that were also studied in this research include the classification of learning methods in general, namely conventional and unconventional learning methods along with their functions and the relevance of these learning methods in PAI subjects according to their time (orde lama, orde baru, and reformasi).